2021
DOI: 10.1016/j.vgie.2021.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Gel immersion endoscopy-facilitated endoscopic mucosal resection of a superficial nonampullary duodenal epithelial tumor: a novel approach

Abstract: Video Video 1 Gel immersion endoscopy-facilitated endoscopic mucosal resection of a superficial nonampullary duodenal epithelial tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
(8 reference statements)
1
8
0
Order By: Relevance
“…These reasons might make snaring difficult and lead to perforation and a low resection rate. However, our previous reports revealed that the buoyancy of mucosal and submucosal layers was favorable and similar to that in underwater endoscopy based on endoscopic ultrasonography findings [19].…”
Section: Accepted Manuscriptsupporting
confidence: 79%
See 3 more Smart Citations
“…These reasons might make snaring difficult and lead to perforation and a low resection rate. However, our previous reports revealed that the buoyancy of mucosal and submucosal layers was favorable and similar to that in underwater endoscopy based on endoscopic ultrasonography findings [19].…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…Furthermore, the viscosity of the gelatinous liquid may possibly affect the opening and closing of the snare. These issues might make snaring difficult and lead to perforation and a low resection rate; however, our previous reports revealed that the buoyancy of the mucosal and submucosal layers was favorable and similar to that in underwater endoscopy based on endoscopic ultrasonography findings [19]. Additionally, there was no difficulty in manipulating the snare.…”
Section: Giermentioning
confidence: 76%
See 2 more Smart Citations
“…In this regard, a key advantage of using gel instead of water is that gel prevents rapid mixing with bowel fluid and narrows the working space based on the appropriate viscosity, especially in difficult anatomical locations 3–5 . Our report demonstrates that the combined use of acetic acid, NBI, and gel immersion contributes toward the complete resection of SSLs located in difficult anatomical locations.…”
Section: Brief Explanationmentioning
confidence: 75%